2022
DOI: 10.1021/acs.iecr.1c04184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steam Treatment on the Properties of Mordenite and Its Catalytic Performance in a DME Carbonylation Reaction

Abstract: A series of dealuminated mordenite (MOR) samples with different acidities and various porosities were prepared through steam treatment of H + /Na + mordenite. The obtained zeolites were elaborately characterized by X-ray diffraction, N 2 adsorption−desorption, scanning electron microscopy, 29 Si nuclear magnetic resonance (NMR), 27 Al NMR, NH 3 temperature-programmed desorption, and Fourier transform infrared spectroscopy, and the catalytic performance for dimethyl ether (DME) carbonylation was investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…166 The Si/Al ratios determined by solid state 29 Si MAS NMR is consistent with that measured by the elemental analysis. 24,72,141 By comparing the values with those obtained by chemical analyses, the (Si/Al) 𝑁𝑀𝑅 amount of extra-framework aluminium can be calculated. However, Equation 1 works well with materials that have framework Si/AI ratios less than about 10.…”
Section: Methods For Determining the Si/al Ratios Of Zeolitesmentioning
confidence: 99%
See 3 more Smart Citations
“…166 The Si/Al ratios determined by solid state 29 Si MAS NMR is consistent with that measured by the elemental analysis. 24,72,141 By comparing the values with those obtained by chemical analyses, the (Si/Al) 𝑁𝑀𝑅 amount of extra-framework aluminium can be calculated. However, Equation 1 works well with materials that have framework Si/AI ratios less than about 10.…”
Section: Methods For Determining the Si/al Ratios Of Zeolitesmentioning
confidence: 99%
“…199,200 Yang and co-workers observed that the dealuminated MOR zeolites exhibited a low catalytic activity but high MeOAc selectivity, indicating that the low BASs density of mordenite is beneficial for the formation of MeOAc. 141 However, a trade-off effect was also observed in the DME carbonylation catalysed by the MOR zeolite, i.e., the conversion of DME increased before the Si/Al ratio reached 11.8 and then decreased with further increasing the Si/Al ratio. 201 More investigations revealed that the strength of the BASs in the 8MR side pockets of MOR zeolite decreased with the increase of Si/Al ratios 202 and the catalytic performance of MOR zeolites on the DME carbonylation is mainly determined by the BASs in the 8MR channels.…”
Section: Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Dealumination rendered positive effects on catalyst activity and stability during the transformation of hydrocarbons. Xu et al [16] reported the preparation of dealuminated mordenites via hydrothermal treatment, and evaluated the catalytic properties of the samples for the carbonylation of dimethyl ether. Viswanadham et al [17] studied the dealumination of mordenite with nitric acid, and observed the increase in the surface area and volume of micropores when the concentration of acid was increased.…”
Section: Introductionmentioning
confidence: 99%